Modeling and Visualization of Flooding in the Wai Lamo River, Kao Barat District, North Halmahera Regency - Kamis, Marlina; Priambodo, Yudit Agus (JURNAL BIOSAINSTEK, 2025)
In the North Maluku Province, specifically in the Kao Barat District of North Halmahera Regency, there is the Wai Lamo River which flows through five villages: Pitago Village, Bailengit Village, Soamaetek Village, Parseba Village, and Tuguis Village. These villages are often affected by flooding due to the river's overflow during heavy rainfall. The purpose of this study is to model the flooding caused by the overflow of the Wai Lamo River, especially in these five villages, and to assess the extent of the flood-affected area. The flood modeling method uses a hydrological approach to simulate water discharge in the river using the HEC-HMS software, and flood inundation areas and affected zones are visualized using GIS with HEC-RAS software. The flood discharge rates obtained from hydrological analysis using HEC-HMS (Hydrologic Modeling System) for return periods of 2, 5, 10, 20, 50, and 100 years at the flood-affected village control points are 115.8 m³/s, 324 m³/s, 550.2 m³/s, 848.5 m³/s, 1376.6 m³/s, and 1897 m³/s, respectively. The results of flood inundation modeling using HEC-RAS (River Analysis System) based on the return period floods show that the overflow of the Wai Lamo River impacts Pitago Village, Bailengit Village, Soamaetek Village, Parseba Village, and Tuguis Village due to their proximity to the riverbanks. Therefore, river embankments and riverbed normalization are required to protect the settlements from the overflow of the Wai Lamo River.